Meßtechnik und Darstellungstechnik in der topographischen Kartographie - Brandstätter, Leonhard (ERDKUNDE, 1968)
There appears to be an inversely proportional relationship between the surveying achievement and cartographic effort in topographic maps. In earlier times, the sporadic network of measurements spurred on to great cartographic achievement. The paucity of geometrical fixed points forced a sharper observation of nature and a finer feeling for drafting technique. However, the technical perfection of relief measurement today, using air photos and exact contours, has found no corresponding advance in the quality of cartographic presentation. Whenever it is sought to pictorially amplify by drawing techniques the completely geometric relief determination, objections are raised. In the opinion of the author, the origins of these objections are to be found in the continued existence of outdated representation techniques and in the neglect of field observation. The accompanying map should show that representation of relief in complete accordance with exact contours and with pictorial clarity is possible.